092. Overview of the Prevalence of Chronic Kidney Disease (CKD) in Kidney and Ureter Stones at Zainoel Abidin Hospital Banda Aceh, 2021 - Saputra, Dwi Wahyu; Mauny, M. Puteh (JBN (Jurnal Bedah Nasional), 2024)
Background : Kidney stones are a predictor and risk factor for CKD and the prevalence rate is 5-10% with comorbid factors which can increase the risk of CKD events. Chronic Kidney Disease (CKD) is a serious complication of urinary tract stones. Chronic kidney disease can occur as a result of urological procedures, obstruction or due to causes inherent in stone formation. Methods : This type of research is descriptive research using secondary data in the form of medical record data. The design of this research is cross sectional with data collection carried out retrospectively. The samples in this study were patients diagnosed with CKD in patients with ureteral stones or kidney stones at Zainoel Abidin Hospital, Banda Aceh. Samples were taken using the total sampling method. Results : In this study, 70 samples were taken and the results of this study based on gender are majority were found to be men 48 samples (68.6%), the most common age category was 41 - 50 years with 28 samples (40.0% ), the most common comorbid factor causing CKD was hypertension in 30 samples (42.5%), the type of urinary tract stones most often found was ureter stones, namely 34 samples (49.0%), and the most common location or urinary tract was ureter stones. bilateral, namely 22 samples (31.4%). Conclusion : The male gender most often experiences CKD due to complications from urinary tract stones, where the age range of 41 - 50 years is the age that experiences the most complications. The most common type of urinary tract stone is ureteral stone with a bilateral location.